Distribution. Known only from the type locality in Eastern Ghats, S India. in Muridae ... - Wilson, Don E.; Mittermeier, Russell A.; Thomas E. Lacher, Jr (Zenodo, 2017)
Distribution. Known only from the type locality in Eastern Ghats, S India. ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Muridae, pp. 536-884 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on page 737, DOI: 10.5281/zenodo.6887260 ...